"At the sharp end": does ambulance dispatch data from south Yorkshire support the picture of increased weapon-related violence in the UK?. Issue 10 (22nd September 2009) - Gray, J T; Walker, A
Abstract : Objective: To assess whether ambulance responses in South Yorkshire to stabbing, gunshot, penetrating trauma cases have increased over the past few years, supporting the observed increase in media reporting. Methods: A review was undertaken of the frequency with which the ambulance medical priority dispatch system card 27 (stab/gunshot/penetrating trauma) was used, grouped by financial year, and comparison made over time and by patient age group. Results: There is a steady increase in the number of occurrences of these cases and also an increase in the percentage made up by the 10–29 year age group. Conclusions: Ambulance data from South Yorkshire support the media conclusion that there is an increase in stabbing, gunshot and penetrating trauma as well as an increase in the proportion of younger victims. This has wider implications for ambulance staff and the UK as a whole; however, these calls remain a low percentage of overall ambulance service activity.